The effect of Metformin on fibrocystic breast disease in women with insulin resistance - E. V. Musina; I. Y. Kogan (ABV-press, 2018)
A little studied question is the development mechanism, timely diagnostics, treatment and prevention of the fibrocystic breast disease at patients with insulin resistance. One of the possible perspective directions of pathogenetic impact on tissues of a mammary gland at the mastopathy associated with a giperinsulinemiya and insulin resistance is use of metformin. Now clinical trials on use of metformin at cancer of mammary glands continue. Data on use of medicines of this group at patients with fibrocystic breast disease in domestic and foreign literature are absent. Objective: assessment of influence of metformin on clinical displays of fibrocystic breast disease and ultrasonic characteristics of a parenchyma of mammary glands at patients with insulin resistance.Materials and methods. As therapy of fibrocystic breast disease patients received metformin in a dose of 1500 mg a day. Dynamic control of a clinical picture of a disease and ultrasonic indicators of a parenchyma of a mammary gland carried out in 3 and 6 months from the beginning of therapy. Results and conclusion. In 6 months of therapy there was a reliable decrease in frequency of a mastalgiya, change of an ultorasound picture of mammary glands: echogenicity of a parenchyma of mammary glands - became sredeny in 95,9% of cases, there was a reliable reduction of thickness of a parenchyma of mammary glands (from 15.5 mm to 10. 5 mm) and diameter of lacteal channels (from 1.7 mm to 0.9 mm). The obtained data on positive influence of metformin on the clinical course of mastopathy and structural changes of a parenchyma of mammary glands at patients with fibrocystic breast disease and insulin resistance allow to consider similar approach as the perspective direction of pathogenetic influence at such pathological association.